QUALITY CHARACTERISTICS OF DRY NOODLES MADE WITH MOCAF AND BANANA FLOUR (Musa sp) - Jejen Pertama Saputra; Hesti Nur'aini; Methatias Ayu Moulina (Jurnal Saintifik (Multi Science Journal), 2026)
This study aimed to analyze the effect of the mocaf and banana flour ratio in making dry noodles. The study used a Completely Randomized Design (CRD) with variations in mocaf and banana flour compositions (80:0, 60:20, 40:40, 20:60, and 0:80). The dry noodles were analyzed for yield, elasticity, moisture content, fat content, fiber content, and organoleptic tests (color, taste, texture, and overall acceptability). The results showed that the treatment with 60% mocaf and 20% banana flour produced dry noodles with the best characteristics, with a moisture content of 10.25%, a fat content of 16.90%, and a fiber content of 10.15%, and the highest panelist preference rating. The business analysis yielded a R/C ratio of 1.3, indicating a profitable business.